Land tenure and agricultural productivity in Ethiopia - Gavian, S. (International Livestock Centre for Africa, 1994)
This research is being undertaken as an ILCA project with support from the Rockefeller Post-Doctoral Fellowship Programme. There are three objectives. One objective is very similar to that of the World Bank and Niger studies: to determine the effects of land tenure on investment, productivity and efficiency in crop-livestock systems in the Ethiopian highlands. The other objectives are: to identify the factors that influence the evolution of land tenure institutions in general and the Ethiopian land tenure systems in particular; and to quantify the prevalence of different types of land related contracts in Ethiopian agriculture and relate the terms of those contracts to household and land attributes. Ethiopia has a very dynamic land tenure situation that makes it very interesting, but also very difficult, to study.